The politics of human rights in East Asia - Christie, Kenneth (Pluto Press, 2001)
Refugees fleeing East Timor. Tiananmen Square in China. The killing fields in Cambodia. Freedom of speech in Singapore. The subject of human rights in Asia is a hotly debated one. In The Politics of Human Rights in East Asia, the authors survey the human rights records and attitudes of each country. The countries covered are: China, Taiwan, Korea, Japan, Indonesia, Myanmar, Cambodia, Vietnam, Thailand, the Philippines, Malaysia and Singapore. Kenneth Christie covers Southeast Asia and Denny Roy covers Northeast Asia. They conclude with a discussion of the Association of East Asian Nation's (ASEAN) role and suggestions for the future. Throughout, they examine the competing meaning of human rights in the Western versus the non-Western context and place the role of human rights within the framework of each country's history and political and economic development.